Traumatic Dental Injuries of Permanent Anterior Teeth in Children referred to Dental School of Tehran University of Medical Sciences: A Retrospective Study: Traumatic Dental Injuries - Zargar, Nazanin; Amiri, Maryam; Mighani, Ghasem (Journal of Dental School, 2023)
Objectives Children frequently encounter dental problems related to traumatic dental injuries (TDIs). This study aimed to investigate TDIs among children aged 7-13 years, who were admitted to the Tehran School of Dentistry in Tehran, Iran. Methods This retrospective study was performed on 70 patients with 129 TDIs. Information, such as age at the time of the accident, gender, cause and type of TDI, the interval between the accident and the emergency care, and treatment, was gathered from the patients’ records. During the follow-up session, the pulp sensibility, probing, and percussion tests were conducted. The collected data was statistically analyzed using Fisher’s exact test and Chi-square test. The significance level was set at P<0.05. Results A total of 129 TDIs were reported during 2018-2021. Maxillary central incisors (80.62%) were the most commonly involved teeth, followed by maxillary lateral incisors (17.82%) and mandibular lateral incisors (1.55%). Falls were the main contributor to TDIs (31.78%). The most frequent TDIs involved enamel-dentin fractures without pulp involvement (37.20%) and subluxation (19.37%), followed by enamel-dentin fractures exposing the pulp (10.85%), avulsion (10.85%), infraction (4.65%), lateral luxation (3.87%), intrusion (3.87%), and extrusion (3.10%). Splinting (26.61%) and restoration (23.74%) were the most frequent treatments. The average follow-up period was 2-3 years, with a survival rate of 67%. Conclusion It appears that a significant number of parents are unaware of the necessity of immediate treatment and regular follow-up after TDIs, which can result in a high rate of treatment failure.